2013
DOI: 10.1007/s00784-013-1168-z
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a portable device for the detection of sleep bruxism

Abstract: These findings are important in the light of the need for simple and reliable portable devices for the diagnosis of SB both in the clinical and research settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(88 citation statements)
references
References 18 publications
0
81
1
6
Order By: Relevance
“…Figure 4 demonstrates no significant difference in the EMG activity between the Q-SB group and the Q-control group classified by the questionnaire, suggesting that evaluation of SB only by a questionnaire was not linked to the actual EMG activity during sleep. It has also been reported that the portable automatic sleep bruxism analysis is considered to be a moderately accurate screening method for sleep bruxism, in spite of the defects that it cannot discriminate tooth grinding from clenching and tends to overestimate the presence of bruxism events [17,[27][28][29]. The signal recognition algorithm of the ambulatory EMG device utilized could help to exclude events unrelated to SB (e.g., grimacing).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 demonstrates no significant difference in the EMG activity between the Q-SB group and the Q-control group classified by the questionnaire, suggesting that evaluation of SB only by a questionnaire was not linked to the actual EMG activity during sleep. It has also been reported that the portable automatic sleep bruxism analysis is considered to be a moderately accurate screening method for sleep bruxism, in spite of the defects that it cannot discriminate tooth grinding from clenching and tends to overestimate the presence of bruxism events [17,[27][28][29]. The signal recognition algorithm of the ambulatory EMG device utilized could help to exclude events unrelated to SB (e.g., grimacing).…”
Section: Discussionmentioning
confidence: 99%
“…The wireless design and small number of components may have contributed to this perception. Moreover, compared with other ambulatory EMG devices (eg), a set‐up procedure for defining thresholds of maximum voluntary contraction (MVC) is not required. This is necessary if scoring of EMG events is based on a % MVC method, which is not the case for BUTLER ® GrindCare ® .…”
Section: Discussionmentioning
confidence: 99%
“…This observational prospective study, involved 53 subjects (27 m, 25 f, 28 ± 13 years) selected among patients referring to the Orthodontics Unit of the Dental School of the University of Torino in the period February-December 2015 requiring an orthodontic treatment. All the subjects were screened for sleep bruxism with a validated portable device (Bruxoff ®, OT Bioelettronica, Torino, Italy) (20)(21)(22)(23)(24). On the basis of this evaluation the subjects were divided into two groups: the case group composed by 20 patients (7 m, 13 f, 25 ± 10 years), and the control group composed by 33 patients (20 m, 13 f, 26 ± 10 years).…”
Section: Methodsmentioning
confidence: 99%